Annotation Bibliography for Geographical Science Field - Sukendra Martha; T Bayuni; A Riyani; E Faridl (Forum Geografi, 1990)
This annotated bibliography is gathered specially for the field of geography obtained from various scientific articles (basic concept in geography) of different geographical journals. This article aims to present information particulary for geographers who will undertake researches, and indeed need the geographical References with all spatial concepts. Other reason defeated by the rapid development of the branch of technical geography such as geographical information systems (GIS) and remote sensing. It hopes that this bibliography can contribute of remotivating geographers to learn and review their original geographical thought.